Thermal study of plants in a dynamic environment using thermovision - Orzechowska, Aleksandra; Szymańska, Renata; Dymek, Jakub; Trela-Makowej, Agnieszka; Trtílek, Martin (Biochemical and biophysical research communications, 2025)
We examined the effect of light-induced heating of leaves in wild-type (Col-0) and tmm-1 Arabidopsis plants. The results showed that the tmm-1 mutant exhibits accelerated cooling of rosettes in response to changes in light intensity, as demonstrated by thermal imaging measurements. This is evident in the time constants determined for temperature kinetics, which were reduced during the transition from light to dark. Our findings indicate that these dynamics can be reliably assessed under various light conditions. Measurements of gas exchange showed that stomatal conductance, transpiration rate, and net CO2 assimilation rate were increased in the tmm-1 mutant. Furthermore, fluorescence analysis revealed that the tmm-1 mutant exhibited an increased ratio of total energy dissipation to the number of active reaction centers, as well as higher average absorption. We also observed that the performance index (PIABS) was reduced compared to Col-0. Nevertheless, the clustering of stomata did not affect the maximum quantum yield of PSII. Our results demonstrate that the maintenance of lower leaf temperatures and the greater cooling capacity in plants with clustered stomata positively affects overall photosynthetic performance.
Keywords: mutace; teplota; listy rostlin; Plant Transpiration; průduchy rostlin; Photosynthesis; Plant Leaves; Mutation; fotosyntéza; Carbon Dioxide; Light; Temperature; Stomatal patterning; oxid uhličitý; Plant Stomata; Arabidopsis; IR thermal imaging; světlo; transpirace rostlin; Light-induced thermal kinetics